2019
DOI: 10.1038/s41598-019-48189-y
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity C-reactive protein to prealbumin ratio measurement as a marker of the prognosis in acute coronary syndrome

Abstract: The study aimed to determine whether high sensitivity C-reactive protein to prealbumin (hs-CRP/PAB) ratio could be used to predict in-hospital major adverse cardiac events (MACE) in patients with acute coronary syndrome (ACS). A total of 659 patients with ACS were included in the study. Patients were divided into two groups: high hs-CRP/PAB ratio group (hs-CRP/PAB ≥0.010) and low hs-CRP/PAB ratio group (hs-CRP/PAB <0.010). MACE was defined as death, cardiogenic shock, re-infarction and acute heart failure. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
(38 reference statements)
1
18
0
1
Order By: Relevance
“…However, their linkages were changed to positive correlations in BD patients after treatment with corticosteroids or immunosuppressants (Fig. 5 d-f), which is in accord with previous reports [ 31 , 32 ] and confirms the association between the increase in inflammation and poor nutrition. However, the clinical utility of these pharmacological linkages has to be validated in different cohorts of BD patients with the follow-up information.…”
Section: Resultssupporting
confidence: 92%
“…However, their linkages were changed to positive correlations in BD patients after treatment with corticosteroids or immunosuppressants (Fig. 5 d-f), which is in accord with previous reports [ 31 , 32 ] and confirms the association between the increase in inflammation and poor nutrition. However, the clinical utility of these pharmacological linkages has to be validated in different cohorts of BD patients with the follow-up information.…”
Section: Resultssupporting
confidence: 92%
“…This study indicates that the high LDL-C risk genotype of rs1799858 (TT + CT) associates with increased levels of the anti-inflammation marker HsCRP. Previous studies have indicated that the HsCRP levels are not only related to cardiovascular disease independent of traditional risk factors, but also can independently predict the occurrence and recurrence of adverse cardiovascular events [37,38]. This study is the first to report that the high risk of increased LDL-C and HsCRP related T allele (TT + CT) of rs1799858 associate with higher risk of new-onset/recurrent AMI (increased approximately by 1.9-fold) after an average follow-up of 51.1-months.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that increased CRP levels provide information on prognosis in conditions such as malignancy, stroke, coronary artery disease (CAD), and heart failure (HF). [4][5][6] Similarly, albumin levels have been documented to provide information on inflammatory conditions. 7 In another study, the CRP-to-albumin ratio was shown to be an independent risk factor for mortality in patients with traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 99%